PENGARUH PELAKSANAAN CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERMASUK DALAM JAKARTA ISLAMIC INDEX - Amalia, Dewi; Permana, Adrian Dwi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2007)
This study is purpose to provide empirical evidence of the influence of applying the corporate governance principle to the financial performance. The examined factors on this research are disclosure, institutional ownership, board of directors, independent board of camisioner, audit committee, and financial performance.The data was collected using purposive sampling method. The number of samples of the company was 11 during the period of 2002-2006. Using a sample of Jakarta Islamic Index, we provide evidence that the corporate governance principle consist of disclosure, institutional ownership, board of directors, independent board of comisioner, and audit committee statistically significant influence to financial performance simultaneously. The result indicate that investors believe that the corporate which used the corporate governance principle as a positive signal ta evaluate the future prospect of the firm.